Factors Influencing the Presentation of Fraudulent Financial Reporting in Indonesia - RIZANI, Fahmi; RESPATI, Novita WeningTyas (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018DO - 10.14505//jarle.v9.1(31).31, 2018)
This study examines the factors that influence the preparation and presentation of fraudulent financial statements basing on the fraud triangle theory . The purpose of this research is to examine and analyze the influences of financial stability (asset change), external pressure, personal financial need (insider ownership), financial targets, ineffective monitoring (by audit committee), and rationalization (auditor’s opinion) on making fraudulent financial statements. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange in 2013 to2015. Sample selection is by purposive sampling. Data used in the analysis was of 147 companies. The data analysis technique for hypothesis testing was by logistic regression analysis. Results of this research indicate that financial stability, external pressure, personal financial need, and rationalization have no significant effect on making fraudulent financial statements. Although the results of this study can not prove the factors that affect fraud in the presentation of financial statements, but companies need to be vigilant to prevent fraud in the presentation of financial statements. Companies must be able to perform early detection of the occurrence of fraudulent financial statements for the survival of the entity.